Digital Transformation of Library Technical Services Through INLISLite: A Qualitative Study in a Regional Public Library - Haruddin, Sri Wahyunita; Yunus, Asraf; Hakim, Abdul (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study analyzes the implementation of INLISLite in technical library services at the Regional Library Office of North Konawe Regency, Indonesia, and identifies supporting and inhibiting factors. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation involving library managers, librarians, and users selected purposively. Data were analyzed through reduction, presentation, and conclusion drawing, guided by innovation diffusion attributes. The findings show that INLISLite supports systematic collection processing, cataloguing, classification, circulation, OPAC publication, data accuracy, and administrative management. Its implementation is supported by perceived usefulness, task compatibility, training, infrastructure, and management support. However, limited digital competence, technical problems, and adaptation from manual procedures remain challenges. This study provides contextual evidence of library information system implementation in a public library in North Konawe Regency, a setting that remains underrepresented in library digitalization research. The findings emphasize the need to strengthen staff capacity, technical assistance, and digital infrastructure to sustain INLISLite-based technical services.